MODEL PENGENDALIAN GERUSAN DI SEKITAR ABUTMEN DENGAN PEMASANGAN GROUNDSILL DAN ABUTMEN BERSAYAP - Didik Purwantoro (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2015)
ABSTRACTThe main aim of this research is to get a control of scouring around the abutmen of bridge. Scouraround the abutments must be controlled because it is the main damage cause of abutments andthe hydraulic structures built in the river bed. This research was carried out using expermentalmethod by standart teaching flume and steady-uniform flow in Hydraulic Laboratory CivilDepartment Yogyakarta State University.. The research is done in clear-water-Scour The abutmentmodel were spillthrough type, wing-wall type, triangular type and semi circular type.The researchresult shows that the good performance of maximum scour depth around the abutment ocurred atwingwall abutment for 4b lenght is equal to 11 cm.Keywords : Scouring, Groundsill, Wingwall abutment